Evaluasi Penerapan Sistem Manajemen Anti Penyuapan (SMAP) pada Inspektorat Jenderal Kementerian A - Zhazha Mia Adelina; Siti Nuryanah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
To implement Presidential Instruction No. 10 of 2016 concerning Actions to Prevent and Eradicate Corruption, the National Standardization Body adopted ISO 37001:2016 concerning the Anti-Bribery Management System (Sistem Manajemen Anti Penyuapan/SMAP) to become SNI ISO 37001:2016. Currently, SMAP has been implemented by government institutions and companies in Indonesia. One of the agencies implementing SMAP is the Inspectorate General of Ministry A. The urgency of implementing SMAP is that the Inspectorate General as the Government Internal Supervisory Apparatus has a risk when conducting an audit that has the potential for negotiations to cover up a problem, so that the audit process made to be vulnerable to bribery. The purpose of this research to evaluate the implementation of the SMAP that has been carried out by the Inspectorate General of Ministry A. This research is case study research with evaluation scenarios using the gap analysis method on 7 requirements clauses based on SNI ISO 37001: 2016 namely Organizational Context, Leadership, Planning, Operations, Support, Performance Evaluation, and Improvement. Gap analysis is used to find out the weaknesses between the current application Conditions and how important the Conditions must be achieved. The results of the study show that the implementation of the Support, Performance Evaluation, and Improvement clauses in terms of implementation still needs to be improved.